Externalisation of domestic economic constraints: China’s spatial fix in Kazakhstan and Turkmenistan - Hidayat Ullah Khan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Growing capital over-accumulation and excessive industrial production have forced policymakers in Beijing to search for profitable outlets overseas. The Belt and Road Initiative (BRI), which focuses on infrastructure connectivity projects across Eurasia, reflects these efforts. This paper theorises BRI as a spatial fix aimed at overcoming the recurring problem of over-accumulation of capital. This paper focuses on BRI-led projects in Kazakhstan and Turkmenistan. By conducting unstructured interviews with experts and examining projects, this paper found that BRI-led projects in Kazakhstan and Turkmenistan not only provided a new geographical space and under-saturated market for Chinese surpluses but also created the demand for Chinese State-Owned Enterprises (SOEs) which were facing a decline in returns. This paper also found that through elements such as non-competitive bidding, embedded conditionality, and double preferential loans, China has successfully stimulated overseas demand for its surpluses. The study, therefore, concludes that BRI-led projects in Kazakhstan and Turkmenistan serve as a spatial fix for China